The Integration of Mind Mapping Technique in Storytelling to Assist EFL students in Mastering Speaking Skill - Nizar Saputra; Muntasir Muntasir (IJELR: International Journal of Education, Language, and Religion, 2021)
This research investigates the effectiveness of mind mapping implementation in storytelling to improve students' speaking skills.  This research was framed as an experimental method in which tests and interviews are used to analyze the data. The test consisted of pre-test and post-test, while the structured interview is used to find out students' perspectives toward using mind mapping in storytelling. The finding suggests a significant difference between students' speaking skills in retelling stories using mind mapping and without mind mapping. This difference could be seen from the distribution of the t-score, which is higher than the t-table. T-score is 6. 8, and the t-table is 1.7. The research also suggests that the students considered the mind mapping technique an excellent and effective technique applied in storytelling to improve their speaking performance. Based on the result, the application of the Mind Mapping Technique in storytelling in teaching speaking skills can be one of effective ways to improve the student's speaking performance.